Comparison of Measured and Monte Carlo Calculated Dose Distributions from Indigenously Developed 6 MV Flattening Filter Free Medical Linear Accelerator - Mishra, Bibekananda (J Med Phys, 2018)
PURPOSE: Monte Carlo simulation was carried out for a 6 MV flattening filter-free (FFF) indigenously developed linear accelerator (linac) using the BEAMnrc user-code of the EGSnrc code system. The model was benchmarked against the measurements. A Gaussian distributed electron beam of kinetic energy 6.2 MeV with full-width half maximum of 1 mm was used in this study. METHODS: The simulation of indigenously developed linac unit has been carried out by using the Monte Carlo-based BEAMnrc user-code of the EGSnrc code system. Using the simulated model, depth and lateral dose profiles were studied using the DOSXYZnrc user-code. The calculated dose data were compared against the measurements using an RFA dosimertic system made by PTW, Germany (water tank MP3-M and 0.125 cm(3) ion chamber). RESULTS: The BEAMDP code was used to analyze photon fluence spectra, mean energy distribution, and electron contamination fluence spectra. Percentage depth dose (PDD) and beam profiles (along both X and Y directions) were calculated for the field sizes 5 cm × 5 cm - 25 cm × 25 cm. The dose difference between the calculated and measured PDD and profile values were under 1%, except for the penumbra region where the maximum deviation was found to be around 3%. CONCLUSIONS: A Monte Carlo model of indigenous FFF linac (6 MV) has been developed and benchmarked against the measured data.